(untitled) (Research, Society and Development, 2023)
This article aimed to make a systematic review about the interconnection between emotional intelligence and transformational leadership. As for the first construct related to the concept of transformational leadership, this can be understood as the leader’s competence in conducting the engagement and motivation of a group of people, and by its adequacy to obtain a cultural transformation with a focus on innovation in companies. Searches were performed for articles indexed in the Scielo and MEDLINE/Pubmed databases, published in the last 10 years (2012-2022). The descriptors, “transformational leadership” and “emotional intelligence”, were used with the Boolean AND search engine to unite the terms. In the end, 6 articles were selected, their data described and their abstracts analyzed through the Descending Hierarchical Classification, processed by the Alceste software. The results showed that the publications about the constructs are recent, dating from 2019. With regard to the findings, three thematic classes emerged: 1) “Types of leadership and emotional intelligence in the context of education”, 2) “Transformational leadership as a mediating factor for increasing the effectiveness of teams”, and 3) “Emotional intelligence of the leader as a significant factor for the performance of employees at work”. In this sense, there was a shortage of productions on the subject in different continents and realities, as well as the need to apply studies in the Brazilian context. In this way, it is considered important to promote research on emotional intelligence and transformational leadership, since these can help in engagement, motivation and effective management of emotions in different sectors, teams and companies.